(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To find out changes in ESR and serum lipid profile in old age male smokers and non-smokers and risk of development of atherosclerosis. Study Design: It is non-interventional and comparative study. Study Period: 1st January to 1st February, 2011 Setting: This study was carried out at the Department of Pathology, Shaikh Zayed Hospital, Lahore. Subjects and Methods: Total 60 males of old age (>65 years) were selected, out of which 30 were smokers and 30 were non-smokers. ESR was done by modified Westergren method and lipid profile was done by chemistry analyzer (Microlab 300 MERCK). Results: A significant increase in serum total cholesterol (TC), low density lipoprotein cholesterol (LDL-c), mean serum triglyceride (TG) and ESR were observed in smokers as compared with non-smokers. While levels of serum high density lipoprotein cholesterol (HDL-c) were significantly lower in smokers as compared with non-smokers. Conclusion: Smoking has an adverse effect on lipid profile and ESR thus enhancing the risk of atherosclerosis.